Pengaruh Profitabilitas terhadap Nilai Perusahaan dengan ESG Performance sebagai Variabel Moderasi - Carolina Dewi Ning Tyas; Andri Prastiwi (Politeknik Ganesha Medan, 2025)
ASEAN is an interesting region for Environmental, Social, and Governance (ESG) research due to the diversity of industrial sectors, and policies that are starting to support ESG adoption and ESG implementation is still at an early stage. This study aims to analyze the effect of profitability on firm value with ESG as a moderating variable in companies in the ASEAN region. The study population consists of 5,530 companies ASEAN listed in the Bloomberg database, with a sample of 661 companies selected using purposive sampling technique based on the completeness of ESG data for the 2019-2023 period. The research method uses a quantitative approach with panel data regression analysis using Eviews 13, where firm value is measured by Tobin's Q, profitability is measured by Return on Assets (ROA), and ESG is measured using ESG scores from Bloomberg which includes environmental, social and governance aspects. The results show that profitability has a positive and significant influence on firm value, and ESG is proven to strengthen the relationship between profitability and firm value. This suggests that good ESG practices can increase operational efficiency, improve corporate image, and provide positive signals to investors. During the study period (2019-2023), several external factors influenced the results, including the COVID-19 pandemic which encouraged companies to better utilize ESG as a crisis protection measure. In addition, evolving ESG regulations and ASEAN capital market characteristics such as small market capitalization and concentrated ownership, form a unique context for ESG implementation. This study concludes that the integration of ESG in corporate strategy not only supports sustainability, but also increases the attractiveness of the company in the eyes of investors, which ultimately contributes to an increase in firm value.